Thin linearly viscoelastic Kelvin-Voigt plates - Christian Licht (2018)
A mathematical model for thin viscoelastic Kelvin-Voigt plates is derived through an asymptotic analysis when the thickness goes to zero. The model involves Kirchhoff-Love kinematics, but the mechanical behavior is no longer of Kelvin-Voigt type: an additional term of delayed memory appears like in homogenization. On propose un modèle mathématique pour les plaques minces viscoélastiques linéaires de Kelvin-Voigt par une étude asymptotique lorsque l'épaisseur tend vers zéro. Le modèle met en jeu une cinématique de Kirchhoff-Love, mais le comportement n'est plus de type Kelvin-Voigt : comme en homogénéisation, un terme additionnel de mémoire longue apparaît. © 2013 Académie des sciences.